IoT Fertigation Dashboard for Precision Agriculture Monitoring and Control - Mohd Darus, Muhamad Syamil Daniel; Mohd Rizalhanafi , Muhammed Akram Irfan; Othman, Maisara (Evolution in Electrical and Electronic Engineering, 2025)
This research involves the development of an IoT-based fertigation dashboard for precision agriculture. A single RS-485 soil sensor was used to measure temperature, moisture, pH, and electrical conductivity. The ESP32 sent this data over Wi-Fi using the MQTT protocol to a Raspberry Pi 5, which acted as the MQTT broker and hosted a real-time dashboard using Node-RED. The system provided live monitoring and remote access. Sensor readings were accurate after calibration, with values like moisture around 10–12%, pH 5.7–6.8, and temperature around 28°C. InfluxDB Cloud was used to store the data online, and it could be downloaded as a CSV file for analysis in Excel. The system was tested successfully, proving to be low-cost, reliable, and suitable for smart farming.